Ion Channel Regulation by Sex Steroid Hormones and Vitamin D in Cancer: A Potential Opportunity for Cancer Diagnosis and Therapy - Restrepo-Angulo, Iván; Bañuelos, Cecilia; Camacho, Javier (Frontiers in Pharmacology, 2020)
Many ion channels are involved in tumor development, promoting cancer cell proliferation, migration, invasion and survival. Accordingly, some of them have been suggested as tumor markers and novel targets for cancer therapy. Some sex steroid hormones (SSH), including estrogens and androgens, favor cancer progression. Meanwhile, other steroid hormones like vitamin D may have anticancer properties. SSH and vitamin D modulate the expression of a number of ion channels in cancer cells from hormone-sensitive tissues, including breast, ovary, prostate, and cervix. Moreover, rapid effects of SSH may be mediated by their direct action on membrane ion channels. Here, we reviewed the SSH and vitamin D regulation of ion channels involved in cancer, and analyzed the potential molecular pathways implicated. In addition, we described the potential clinical use of ion channels in cancer diagnosis and therapy, taking advantage of their regulation by SSH and vitamin D. Since SSH are considered risk factors for different types of cancer, and ion channels play important roles in tumor progression, the regulation of ion channels by SSH and vitamin D may represent a potential opportunity for early cancer diagnosis and therapeutic approaches in SSH and vitamin D sensitive tumors.